Study of efficacy of ischemia reversal program (IRP) in ischemic heart disease (IHD) patients with VO2max and Duke’s treadmill score - Sane, Rohit; Sugwekar, Varada; Nadapude, Aarti; Hande, Archana; Depe, Gayatri; Mandole, Rahul (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Number of people dying from IHD has increased from 0.61 million in 1990 to 1.13 million in 2010, which is a disturbing fact. According to report by World Health Organization, India would be spending a whopping 237 billion US dollars, owing to direct spending on health care and indirectly due to loss of productivity due to IHD. Ischemia Reversal Program (IRP) is a combination of Panchakarma and allied therapy. This study was conducted to evaluate the effect of IRP on VO2max, Duke’s treadmill score, systolic blood pressure (SBP), diastolic blood pressure (DBP), and dependency on conventional therapy in IHD patients. Methods: This observational study was conducted in January 2017, wherein the data of IHD patients (inducible ischemia on stress testing) who attended out-patient departments (OPDs) at Madhavbaug clinics in Maharashtra, India were identified. Data of patients who were administered IRP (60-75 minutes) with minimum 7 sittings over 90 days (±15 days) were considered. Variables were compared between day 1 and day 90 of the IRP. Results: Out of 38 enrolled patients, 25 were males while 13 females. There was significant improvement in Duke’s score with subjects at moderate (50%) and high (31.6%) risk at baseline were significantly decreased to low (52.6%) and moderate (47.4%) after the 90th day of therapy. IRP also showed significant improvement in VO2max by 9.11 (from 20.29±6.72 to 29.40±6.71; p<0.001), SBP by 5.78 (from 128.78±17.40 to 123±12.23, p<0.03), DBP by 4.76 (from 80.53±8.10 to 75.76±6.85, p<0.005). Dependency on concomitant medicines was reduced. Conclusions: IRP was effective in IHD; it had dual benefits, i.e. anti-ischemic effect, as well as reducing the dependency on allopathic medicines.